Multimedia and Conventional Learning in Students with Visual and Auditory Learning styles: Experiments on Learning Outcomes - Gani, Arsyad Abd; Ibrahim, Nurdin; Khaerudin, Khaerudin (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aims to compare the learning outcomes of students in the experimental and control class with visual and auditory learning styles through the use of multimedia during learning. This research is a comparative quantitative study with the subject of the study consisting of 50 students divided equally in the two classes. Then the hypothesis test was carried out using the two-way ANOVA test. Based on the results of the study it was found that there were differences in learning outcomes of students who were taught with multimedia and those taught with conventional media both those using auditory and visual learning styles. Therefore, the changing paradigm of teaching for integrated social science teachers (history, geography, and economics) should consider the quality and quantity of multimedia, then the creativity and innovation of teachers is absolutely necessary in planning, implementing and evaluating the use of multimedia in learning.